Bride Price and Fertility Decisions: Evidence from Rural Senegal - Linguère Mously Mbaye; Natascha Wagner (Institute for the Study of Labor (IZA), 2013)
This paper is the first to provide evidence about the relationship between bride price payments and fertility decisions in the African context. Remarkably, the results show that bride price payments reduce fertility pressure, with a woman reducing her number of children by 0.5 at the mean bride price. The results are robust to different tests that we conduct to address the potential endogeneity between bride price payments and fertility decisions. As possible transmission channels, we find that poor women and men with low levels of education are the most negatively affected by the tradition of bride price payments. Furthermore, a lower bride price payment increases fertility pressure in polygamous households and for arranged marriages, while the bride price payment has no effect on the couple's decisions concerning fertility in monogamous households and for love marriages. Consequently, given that bride price payments have less power over (economically) independent women, empowerment will give leeway to girls in traditional societies, even if the bride price system is not overturned.
Keywords: O12; Z13; 330; bride price; empowerment; fertility; marriage payments; Senegal